2014
DOI: 10.4238/2014.november.27.21
|View full text |Cite
|
Sign up to set email alerts
|

Development-related expression patterns of protein-coding and miRNA genes involved in porcine muscle growth

Abstract: ABSTRACT. Muscle growth and development is associated with remarkable changes in protein-coding and microRNA (miRNA) gene expression. To determine the expression patterns of genes and miRNAs related to muscle growth and development, we measured the expression levels of 25 protein-coding and 16 miRNA genes in skeletal and cardiac muscles throughout 5 developmental stages by quantitative reverse transcription-polymerase chain reaction. The Short Time-Series Expression Miner (STEM) software clustering results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…MiR-499-5p was a breed-DE miRNA found at 40, 55, 70, and 90 dpc in the present study, and its expression level gradually down-regulated over time. A recent study showed that miR-499 exhibits a greater expression level in psoas major muscle compared with the longissimus muscle, which respectively have higher proportions of red and white skeletal muscle in pigs [ 55 ]. And there was a substantial loss of type I muscle fibers and a concomitant increase in the expression of faster types IIx and IIb muscle fiber in the soleus of double knockout mice for miR-208b -/- and miR-499 -/- ; while the overexpression of miRNA-499 resulted in higher proportions of type I muscle fiber [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-499-5p was a breed-DE miRNA found at 40, 55, 70, and 90 dpc in the present study, and its expression level gradually down-regulated over time. A recent study showed that miR-499 exhibits a greater expression level in psoas major muscle compared with the longissimus muscle, which respectively have higher proportions of red and white skeletal muscle in pigs [ 55 ]. And there was a substantial loss of type I muscle fibers and a concomitant increase in the expression of faster types IIx and IIb muscle fiber in the soleus of double knockout mice for miR-208b -/- and miR-499 -/- ; while the overexpression of miRNA-499 resulted in higher proportions of type I muscle fiber [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to miR-434-3p, other miRNAs that play important roles in skeletal muscle have also been identified using miRNA microarrays. Among these miRNAs, miR-499 enhances the expression of the β-myosin heavy chain, which promotes muscle development 39 . Let-7 mutants exhibit temporal misregulation of NMJ maturation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the dynamic genetic changes starting from newborn to two months old, STEM analysis was performed using the transcriptomic data of the LD muscle samples at the four time points. The STEM analysis provides a new approach to cluster, compare and visualize gene expression data from short-time series RNA-seq or microarray experiments [ 27 ], which has been widely used in studying the dynamic transcriptomic changes during development in pigs [ 28 30 ]. After adjusting a series of parameters, we found that setting the maximum number of model profiles to 2 and retaining the default values of the other parameters were optimal, as eight significantly different expression profiles were found to contain most of the DEGs.…”
Section: Discussionmentioning
confidence: 99%